The Pragmatics of Irish English 2005
DOI: 10.1515/9783110898934.141
|View full text |Cite
|
Sign up to set email alerts
|

Offering in Ireland and England

Abstract: and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying the publication in the public portal ? Take down policyIf you believe that this document breaches c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 9 publications
(7 reference statements)
5
36
1
Order By: Relevance
“…Specifically, Barron (2005) found that IrE speakers favour reference to preparatory conditions for requests in comparison with English English speakers. Connington (2005) also found that IrE speakers prefer interrogative structures for requests, offers and instructions.…”
Section: According To O'keeffe and Adolphsmentioning
confidence: 95%
“…Specifically, Barron (2005) found that IrE speakers favour reference to preparatory conditions for requests in comparison with English English speakers. Connington (2005) also found that IrE speakers prefer interrogative structures for requests, offers and instructions.…”
Section: According To O'keeffe and Adolphsmentioning
confidence: 95%
“…O'Keeffe, McCarthy and Carter (2007) and Barron (2005) have looked at this in greater detail through corpus-based analyses and discourse completion tasks, respectively. The following exchange from LCIE shows how this reoffering manifests and hence the use of will in its manifestation: (9) We see a directness about the offering and reoffering.…”
Section: Teaching Irish English?mentioning
confidence: 99%
“…The following exchange from LCIE shows how this reoffering manifests and hence the use of will in its manifestation: (9) We see a directness about the offering and reoffering. As O'Keeffe et al (2007) and Barron (2005) note, it is a cultural norm of politeness in Irish English to refuse a first offer. This poses a challenge for offers of food, etc.…”
Section: Teaching Irish English?mentioning
confidence: 99%
“…It should be noted, however, that the recent years have witnessed a rapid growth in the number of studies, within the framework of 'variational pragmatics' (Schneider & Barron (2008), on two or more varieties of English in the realization of speech acts such as offers (Barron, 2005), responses to thanks (Schneider, 2005), requests (Barron, 2008), expressions of gratitude (Jautz, 2008), etc. Nevertheless, a great deal of work still remains to be done on speech act patterns in Canadian English.…”
Section: Introductionmentioning
confidence: 99%